In Airbnb we trust: Understanding consumers’ trust-attachment building mechanisms in the sharing economy - Yang, Sung-Byung; Lee, Kyungmin; Lee, Hanna; Koo, Chulmo (International journal of hospitality management, 2019)
•This study develops on the trust building model and attachment theory in the sharing economy environment.•It investigates how users build trust-attachment relationships through cognitive- and affective-based trusts.•It also examines how users intend to use the sharing economy service through identity- and bond-based attachments.•The cognitive trust-identity attachment building mechanism rather than the affective trust-bond one.•It suggests how to enrich users’ trust-attachment toward the firm and the service provider. The sharing norm has enabled many of unused resources revamped and returned with some value to both travelers and local communities in the sharing economy. Airbnb requires remarkable trust that goes beyond the level where both user and host take risks from a sharing transaction. This paper suggests an empirical research model developed based on the trust building model and attachment theory explaining how users develop their trust and further attachment through two major routes. The results indicate that the cognitive trust-identity attachment building mechanism is more effective than affective trust-bond attachment depending on the emotional distance between the users and hosts. Finally, this paper provides scholars with theoretical enhancement on the trust and attachment literature and recommends managers of the sharing businesses to enrich users’ trust-attachment toward the firm and the service provider that has a strong influence on users’ behavioral intention to use.